Permintaan Ekowisata Bahari (Snorkeling dan Diving) dan Valuasi Sumber Daya Terumbu Karang di Taman Nasional Karimunjawa - Amalia Febryane Adhani Mazaya; Fredinan Yulianda; Taryono Taryono (Institut Pertanian Bogor, 2020)
Karimunjawa National Park was designated as a Marine National Park area since the enactment of Kepdirjen PHKA No. SK. 28/IV-SET/2012. The marine tourism utilization zone covers 2.45% of the total area of TNKJ. One of the great potential resources that is utilized in tourism utilization zone is coral reefs. Economic valuations of coral reefs are considered necessary as an approach to show the benefits of coral reef ecosystem management policy making and provide useful information for marine tourism development. Marine ecotourism activities in TNKJ are snorkeling and diving. To know the factors influencing marine ecotourism activity of TNKJ, the Travel Cost Method was used to presume the consumer surplus. This information is used as an input or consideration to manage the coral reef resources for marine ecotourism activity of TNKJ. Based on correlation and regression analysis, marine ecotourism demand is influenced by travel cost, age, education, income, gender, long trip, and distance. Marine snorkeling tourism are significantly (α=0,05) influenced by gender and duration of travel with coefficient values of -1,2325 and -0,1942. The demand model of snorkeling tours to travel cost is y = 11.831.242,4107x-7,8684 with consumer surplus of IDR94549/person. Diving marine tourism is significantly (α=0.05) influenced by travel cost, trip length, and distance with coefficient value of -1.23E-06, -0.0947, and 0.0033. The demand model to travel cost is y = 2.363.272,7634x-0,9236 with consumer surplus of IDR29254/person. Based on these results, marine ecotourism of snorkeling and diving of TNKJ has the potential to be developed in economic terms through the determination of entrance fee. Keywords: coral reefs, economic value, Karimunjawa National Park, marine ecotourism